2004
DOI: 10.1167/iovs.04-0629
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Higher-Order Aberrations and Contrast Sensitivity after Conventional Laser In Situ Keratomileusis

Abstract: Conventional LASIK significantly increases ocular higher-order aberrations, which compromise the postoperative contrast sensitivity function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
137
3
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(148 citation statements)
references
References 39 publications
4
137
3
4
Order By: Relevance
“…7,12,16,[26][27][28] Eyes with cataract have decreased contrast sensitivity and increased higher-order aberration. 12 Applegate et al 16 reported that the area under the contrast sensitivity function decreases as the wavefront variances increase after radial keratotomy.…”
Section: Discussionmentioning
confidence: 99%
“…7,12,16,[26][27][28] Eyes with cataract have decreased contrast sensitivity and increased higher-order aberration. 12 Applegate et al 16 reported that the area under the contrast sensitivity function decreases as the wavefront variances increase after radial keratotomy.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Recent studies using wavefront analysis technology reported that higher-order aberrations (HOAs) significantly increase after refractive procedures such as radial keratotomy, 14 photorefractive keratectomy, 15 and laser in situ keratomileusis. 16 These increases are known to be related to the deterioration of visual function. [14][15][16] However, no reports have addressed the changes in ocular aberrations after scleral buckling surgery by search using Pub Med.…”
Section: Introductionmentioning
confidence: 99%
“…16 These increases are known to be related to the deterioration of visual function. [14][15][16] However, no reports have addressed the changes in ocular aberrations after scleral buckling surgery by search using Pub Med. We conducted the current prospective study to quantitatively evaluate changes in HOAs after scleral buckling surgery for the treatment of RD.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrationen höherer Ordnung durch konventionelle refraktivchirurgische Korrekturen nachgewiesen werden (Marcos 2001, Moreno-Barriuso et al 2001, Panagopoulou und Pallikaris 2001, Miller et al 2002, Llorente et al 2004, Spitzlberger 2004, Yamane et al 2004). …”
Section: Als Ursache Dieser Postoperativen Sehverschlechterung Konnteunclassified
“…Für diese Studie wurden zur genauen Betrachtung der Aberrationen die ZernikeKoeffizienten bis einschließlich der vierten Ordnung ausgewählt (Liang und Williams 1997, Artal et al 2001, Panagopoulou und Pallikaris 2001, Cheng et al 2003b, Fam und Lim 2004, Yamane et al 2004, Zhu et al 2004). …”
Section: Durchführung Der Messungenunclassified